Sei sulla pagina 1di 6

MATH 314: Homework 1

Begad Houty
August 31, 2018

1. Prove that P (n) = 4n2 − n = 3 + 11 + · · · + (8n − 5). (using Induction)

Base Case: For n = 1, P (1) = 4(1)2 − 1 = 3 and 8n − 5 = 8(1) − 5 = 3. Thus, the


base case holds.
Inductive Step: Assuming P (n) holds, P (n + 1) = 4(n + 1)2 − (n + 1) = 3 + 11 + · · · +
(8(n + 1) − 5).

3 + 11 + · · · + (8(n + 1) − 5) = 4(n + 1)2 − (n + 1)


4n2 − n + (8(n + 1) − 5) = 4n2 + 7n + 3
4n2 + 7n + 3 = 4n2 + 7n + 3
Conclusion: Since the base case holds and the formula holds for n+1 holds as well, then
P (n) hold for n ≥ 1.

2. (a)
S = 1 + 3 + · · · + (2n − 1)
S = (2n − 1) + · · · + 3 + 1
Adding both equations, we get 2S = n(2n). Therefore, the sum of positive odd numbers
is n2 .

2. (b) Prove that P (n) = n2 = 1 + 3 + · · · + (2n − 1). (using Induction)

Base Case: For n = 1, P (1) = (1)2 = 1 and 2n − 1 = 2(1) − 1 = 1. Thus, the base
case holds.
Inductive Step: Assuming P (n) holds, P (n + 1) = (n + 1)2 = 1 + 3 + · · · + (2(n + 1) − 1).

1 + 3 + · · · + (2(n + 1) − 1) = (n + 1)2
n2 + (2(n + 1) − 1) = n2 + 2n + 1
n2 + 2n + 1 = n2 + 2n + 1
Conclusion: Since the base case holds and P (n + 1) holds as well, then P (n) holds for
n ≥ 1.

1
3. Prove that P (n) = 7n − 6n − 1 is divisible by 36. (using Induction)

Base Case: For n = 1, P (1) = 71 − 6(1) − 1 = 0 which is divisible by 36. Thus, the
base case holds.
Inductive Step: Assuming P (n) holds, P (n + 1) = 7n+1 − 6(n + 1) − 1.

7n+1 − 6(n + 1) − 1
7(7n ) − 6(n + 1) − 1
7(7n ) − 6n − 7 − 36n + 36n
7(7n − 6n − 1) + 36n
Since P(n) is assumed to be divisible by 36 and 36n is is divisble by 36, P (n + 1) =
7(7n − 6n − 1) + 36n is divisible by 36.
Conclusion: Since the base case holds and P (n + 1) holds as well, then P (n) holds for
n ≥ 1.

4. (a) Prove that n2 > n + 1 for n ≥ 2. (using Induction)

Base Case: For n = 2, 22 > 2 + 1. Base case holds.


Inductive Step: Assuming n2 > n+1 is true (Inductive Hypothesis), prove that (n+1)2 >
(n + 1) + 1 .

n2 > n + 1
n2 + 2n + 1 > n + 1 + 2n + 1
(n + 1)2 > 2n + ((n + 1) + 1) > (n + 1) + 1
Conclusion: Since the base case holds and P (n + 1) holds as well, then P (n) holds for
n ≥ 2.

4. (b) Prove that n! > n2 for n ≥ 4. (using Induction)

Base Case: For n = 4, 4! > 42 . Base case holds.


Inductive Step: Assuming n! > n2 is true (Inductive Hypothesis), prove that (n + 1)! >
(n + 1)2 .

n! > n2
(n + 1)n! > (n + 1)n2
(n + 1)! > (n + 1)n2
From 1.8(a), n2 > n + 1. So by extension, (n + 1)n2 > (n + 1)2 . Thus, (n + 1)! > (n + 1)2
Conclusion: Since the base case holds and P (n + 1) holds as well, then P (n) holds for
n ≥ 4.

√ 1/3 p
3

5. Show that (5 − 3) is irrational. Let a = 5 − 3

2

a3 = 5 − 3

5 − a3 = 3
(5 − a3 )2 = 3
If a is rational, then 5 − a3 is rational as well and thus the equation x2 = 3 for x = (5 − a3 )
must have rational roots. However, by the Rational Zeros Theorem, the only possible
rational roots for x2 − 3 = 0 are x = ±1, ±3. Those values for x are not roots to the
equation, thus a is irrational.

6. By the Rational Zeros Theorem, the only possible rational roots of f (x) = x8 − 4x5 +
13x3 − 7x + 1 are x = ±1. f (1) = 4 and f (−1) = 0 thus x = −1 is the only rational root
of f(x).

7. (iv) Show that (−a)(−b) = ab for all a,b.

a + (−a) = 0 (A4)
a(−b) + (−a)(−b) = 0(−b) (DL)
−ab + (−a)(−b) = 0 (iii,ii)
ab + (−ab) + (−a)(−b) = ab (A3)
(−a)(−b) = ab (A4,A3)

7. (v) Show that if ac = bc, then a = b.

ac = bc
acc = bcc−1
−1

a(cc−1 ) = b(cc−1 ) (A1x2)


a(1) = b(1) (A4x2)
a=b (A3x2)

8. (v) Prove that 0 < 1.


From 3.4 (iv), 0 ≤ a2 for all a. If we take a = 1, 0 must be either less than or equal to 1.

Now we need to show that 0 6= 1. Lets assume 1 = 0 and a as any real number.

1=0
a·1=a·0
a=0 (A3,3.1(ii))

However, a should be any real number not just 0. Thus, 1 6= 0 (proof by contradiction)
and 0 < 1.

8. (vii) Prove that if 0 < a < b, then 0 < b−1 < a−1 .
Subgoal(1): From 3.4 (vi), If 0 < a, then 0 < a−1 . Therefore, since 0 < b, then 0 < b−1 .

Subgoal(2): We need to prove that if a < b, then b−1 < a−1 .

3
a<b
a(b a ) < b(b−1 a−1 )
−1 −1

(aa−1 )b−1 < (bb−1 )a−1 (M2 and M1 ,M1)


1 · b−1 < 1 · a−1 (M4x2)
b−1 < a−1 (M3x2)

We have proved that 0 < b−1 in subgoal(1) and b−1 < a−1 in subgoal(2). Using both
subgoals, we have proved our original goal of 0 < b−1 < a−1 .
9. (a) Prove |a + b + c| ≤ |a| + |b| + |c| for all a, b, c ∈ R.
|a + b + c| = |(a + b) + c| (A4)
≤ |a + b| + |c| (Triangular Identity)
≤ |a| + |b| + |c| (Triangular Identity)

Pn Pn
9. (b) Prove | i=1 ai | ≤ i=1 |ai | for all ai ∈ R.
Base Case: For n = 1, |a1 | ≤ |a1 | is true. Thus, the base case holds.

Pn Pn Pn+1 Pn+1
Inductive Step: Assuming | i=1 ai | ≤ i=1 |ai |, prove | i=1 ai | ≤ i=1 |ai | .

n
X n
X
| ai | ≤ |ai |
i=1 i=1
n
X Xn
| ai | + |an+1 | ≤ |ai | + |an+1 |
i=1 i=1
n+1
X n+1
X
| ai | ≤ |ai | (Triangular Identity)
i=1 i=1

Pn
Conclusion: Since the base case holds and the inductive step holds as well, then | i=1 ai | ≤
P n
i=1 |ai | holds for n ≥ 1.

10. The argument fails for n = 1 in the inductive step. For a set that contains 2 cows
(P (n + 1)), we can form 2 sets that contain 1 cows (n cows). However, both sets have
different distinct cows and don’t have any cows common between them. Thus, we cannot
prove that those 2 cows in the set have the same color and the whole argument fails.
11. Find the negation of the 3rd order axiom: ∀a, b, c ∈ N : a ≤ b ∧ b ≤ c =⇒ a ≤ c.

¬(∀a, b, c ∈ N : a ≤ b ∧ b ≤ c =⇒ a ≤ c)
∃a, b, c ∈ N : ¬(a ≤ b ∧ b ≤ c =⇒ a ≤ c)
∃a, b, c ∈ N : a ≤ b ∧ b ≤ c ∧ ¬(a ≤ c)
∃a, b, c ∈ N : a ≤ b ∧ b ≤ c ∧ a > c

4
R∞
12. Prove Γ(n) = 0
tn−1 e−t dt = (n − 1)!
Base Case: For n = 1, (n − 1)! = (1 − 1)! = 0! = 1
Z ∞
Γ(1) = t0 e−t dt
0
Z R
= lim e−t dt
R→∞ 0
= lim −e−t |R
0
R→∞
= 0 + e0
=1

Therefore, the base case holds since Γ(1) = (1 − 1)! = 1.


R∞
Inductive Step: Assuming Γ(n) = 0 tn−1 e−t dt = (n − 1)!, prove that Γ(n + 1) =
R ∞ n −t
0
t e dt = n! .

Z ∞
Γ(n + 1) = tn e−t dt
0
Z R
= lim −ntn−1 e−t |R
0 + lim ntn−1 e−t dt (Integration by parts)
R→∞ R→∞ 0
Z R
= 0 + n lim tn−1 e−t dt (L’hopital’s Rule)
R→∞ 0
= n(n − 1)! (Induction Hypothesis)
= n!

R ∞ n−1 −t Since the base case holds and the inductive step holds as well, then Γ(n) =
Conclusion:
0
t e dt = (n − 1)! holds for n ≥ 1.

13. (a) Prove the first 3 order axioms for | instead of ≤ ∀a, b, c ∈ N.

O1. Given a and b, either a|b or b|a. (False)


Assume that a, b ∈ P and a 6= b. By the definition of prime numbers, the only numbers
that divide b are 1 and b. Since a 6= 1 because a ∈ P and a 6= b, thus a - b and O1 fails.

O2. If a|b and b|a, then a = b(True).


By definition of divisibilty, ∃q, r ∈ N : b = aq ∧ a = br if a|b and b|a is true.

a = bq
ar = bqr
b = bqr
1 = qr M4x2, then M3x2
r−1 = q M3,M4

However, the only number in N that has a multiplicative inverse is 1. Thus, r−1 = q =
1 = r. We finally arrive at a=b and b=a when q and r are substituted in a=bq and b=ar.

5
O3. If a|b and b|c, then a|c.(True) By definition of divisibilty, ∃q, r ∈ N : b = aq ∧ c = br
if a|b and b|c is true.

c = br
c = aqr

Since N is closed under multiplication, then qr ∈ N. Thus, using the definition of divisi-
bility and c = aqr, a|c.

13. (b) Prove that if p ∈ P and p|n then p - n + 1.


Assume p|n + 1 is true if p ∈ P and p|n. Then by definition of divisibilty, ∃q, r ∈ N : n =
pq ∧ n + 1 = pr.

pq + 1 = pr
q + p−1 = r M4x2,DL,M3x3

We seemed to have reached a contradiction because p−1 ∈ / N and q +p−1 ∈


/ N.However,r ∈
N. As a result of contradiction, p|n + 1 must be false.

13. (c) Let’s assume there are a finite number of prime numbers in a set P. If we take the
product of all the elements in S and add 1 (Let’s name it x), we get a number that is in
the set of natural numbers. However, this number can’t be divided by any of the elements
of set P due to the result in Q13(b). Using axiom P2 and the definition of prime, x must
be a prime number which is not in set P. As a result, for any finite set of prime numbers,
there must be a prime number in the set of natural numbers that is not in P. Therefore,
the set of prime numbers is infinite.

13. (d) Prove that if n ≥ 2, then n can be factored into a product of primes.(using strong
induction)
Base Case: For n = 2, 2=2. Thus, the base case holds.
Inductive Step: Assuming that a number n can be factored into a product of primes for
2 ≤ n ≤ k where k ∈ N. Prove that k+1 can also be factored into a product of primes.

k+1 can either be prime or composite. So,


1) If k+1 is prime, then k+1 is already in its prime factored form.
2) If k+1 is composite, then by the axiom P2, there exist a prime number p where p|k + 1.
By definition of divisibility, k + 1 = pq for q ∈ N. Moreover, using O5, q ≤ k + 1 and
thus 2 ≤ q < k. Due to the assumption in the begining of the inductive step, q can be
factored into a product of primes and therefore pq is a product of primes (meaning k+1
can be factored into a product of primes).
Conclusion: Since the base case and the inductive step hold for n ≥ 2, then n can be
factored into a number of primes for any n ≥ 2 .